MEDINA, Jaume (2013). Sobre Ramon Llull - Núria Gómez Llauger (Enrahonar: Quaderns de Filosofia, 2015)
Medina, Jaume (2013) Sobre Ramon Llull Barcelona: Llibres de l’Índex, 322 p. ISBN 978-84-940712-4-9